Rethinking excessive habits and addictive behaviors - Bevacqua, Tony. (Lanham : Rowman & Littlefield, 2015)
Twelve-step programs are one of the most popular ways of treating addiction, but are they the best? Here, Tony Bevacqua questions the efficacy of these approaches and offers a different way of looking at addiction that takes into account his work with clients in his private practice and other studies done on the notion of addiction as a disease. Breaking new ground in the area of addiction, his work will offer clients and practitioners an alternative route forward.
The origins of the AA mindset -- Changing our language, changing our subjectivity -- The reality of human experience -- Love, approval, and validation -- Rethinking excessive habits and addictive behaviors -- Deconstructing deficit-based language -- Pharmaceutical drugs and the DSM-5 -- Celebrity culture and addictive behavior -- Parenting influence on children -- The "love" we learned -- Subjective well-being: the goal of all positive outcomes -- Rethinking your life challenges and experiences -- New learning, new direction.
Includes bibliographical references and indexes.
Keywords: Compulsive behavior; Substance abuse